(untitled) (IASH Indian Journal of Arid Horticulture, 2025)
The recognition of diversity among plant species highlights the importance of utilizing neglected and underutilized plants, which play a crucial role in ensuring food security, providing livestock feed, generating income, and meeting the energy re quirements of rural communities. This approach promotes sustainable food security by diversifying our food sources, rather than depending solely on staple crops, which can create a limited food supply and increase vulnerability. Although dietary diver sification and the supply of essential micronutrients like vitamins and minerals hold significant promise for reducing risks in agricultural production systems, they’re main underexplored in research and development. This neglect may result in genetic erosion. Ziziphus nummularia is a plant species whose entire structure-fruits, leaves, branches, and roots-holds considerable economic value in rural communities. For instance, ripe fruits are consumed fresh, leaves serve as fodder, thorny branches are used for fencing farm boundaries, and wood is utilized for fuel and the creation of local agricultural tools, in addition to its applications in traditional medicine. In addition, this plant is capable of thriving under environmental pressures such as high temperatures, significant wind speeds, and low moisture availability, making it appropriate for cultivation in regions with adverse natural conditions, such as deteriorating land and limited water supplies. The limited research conducted on Z. nummularia has further complicated efforts to develop superior varieties within this species. In the future, it is crucial to conduct studies that fully leverage the potential of this species. This article is designed to provide a comprehensive overview of Z. nummularia, with the intention of inspiring researchers to explore this crop, which is vital in India and other arid and semi-arid areas around the world.